2005
DOI: 10.1002/jmv.20536
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of human G9 rotavirus with an exceptionally high frequency in children admitted to hospital with diarrhea in Chiang Mai, Thailand

Abstract: Among 315 fecal specimens collected from children hospitalized with diarrhea in Chiang Mai, Thailand, in 2000-2001, group A rotavirus was detected in 107 (34.0%). Of these, 98 (91.6%) were G9, 6 (5.6%) were G3 and 3 (2.8%) were G2, respectively. Identification of their P-types demonstrated that 103 (96.3%) were P[8], 3 (2.8%) were P[4], and 1 (0.9%) was P[3] genotypes. Determination of G- and P-type combination revealed that all of G9 isolates were associated with P[8]. G9P[8] was the most predominant genotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
50
3

Year Published

2006
2006
2010
2010

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 45 publications
5
50
3
Order By: Relevance
“…Although epidemiological surveillance and genotype identification of rotavirus infections in human and pig populations in Chiang Mai, Thailand, have been carried out extensively over the past two decades, the P[10] genotype had never been reported previously [Maneekarn and Ushijima, 2000;Maneekarn et al, 2006;Khamrin et al, 2006bKhamrin et al, , 2007cChan-It et al, 2008]. The present study conducted in 2005 described the detection of an unusual strain of G3P[10] (CMH079/05) in a 2-year-old boy admitted to hospital with acute gastroenteritis.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Although epidemiological surveillance and genotype identification of rotavirus infections in human and pig populations in Chiang Mai, Thailand, have been carried out extensively over the past two decades, the P[10] genotype had never been reported previously [Maneekarn and Ushijima, 2000;Maneekarn et al, 2006;Khamrin et al, 2006bKhamrin et al, , 2007cChan-It et al, 2008]. The present study conducted in 2005 described the detection of an unusual strain of G3P[10] (CMH079/05) in a 2-year-old boy admitted to hospital with acute gastroenteritis.…”
Section: Discussionmentioning
confidence: 88%
“…The studies of rotavirus infection carried out in Thailand revealed that rotaviruses are the leading etiologic pathogens that causes diarrhea in children, and are responsible for about 27-58% of diarrheal diseases in hospitalized cases [Maneekarn and Ushijima, 2000;Jiraphongsa et al, 2005;Khamrin et al, 2006b]. Epidemiological surveillance of group A rotavirus infection conducted in Chiang Mai, Thailand, during the period of 2000-2004 [Khamrin et al, 2006b[Khamrin et al, , 2007c During these extensive epidemiological studies, rotavirus strains with unusual G-P combinations were occasionally detected in children hospitalized with acute gastroenteritis; for example, an unusual strain of human rotavirus G3P[3] (CMH222) bearing simian-like VP7 and caprine-like VP4 genes was isolated from a 2-year-old child patient in 2001 [Khamrin et al, 2006a].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specific genotypes, such as G9 and G12, are emerging in various parts of the world (9,28,33,39,40,45,47). Outbreaks of rotavirus infections have been described, and these also require adequate genotype identification tools (18,46,50).…”
Section: Discussionmentioning
confidence: 99%
“…Rotavirus G9 has emerged as a common global strain [Ramachandran et al, 1998;Santos et al, 2001;Das et al, 2002;Armah et al, 2003;Kirkwood et al, 2003;Reidy et al, 2005;Khamrin et al, 2006] and other genotypes including G5, G8, G10, and G12 are increasingly reported globally [Beards and Graham, 1995;Santos et al, 1998;Das et al, 2003;Fischer et al, 2003;Laird et al, 2003;Castello et al, 2006;Samajdar et al, 2006;Volotao et al, 2006]. Genetic molecular analyses have been conducted previously to investigate whether changes in the genotypes over time could be explained by corresponding genetic changes on the VP7 gene.…”
mentioning
confidence: 99%